Qualitative Study to Determine the Meaning of Emergencies among Elderly People in The Community - Raksaken, Napachanok; Nuntaboot, Khanitta (Jurnal Keperawatan Soedirman, 2024)
Emergency services play a vital role in addressing the needs of the elderly in the community. Proper adjustments to service policy are necessary, but the current policies fail to adequately address these needs. This study investigated the emergency needs of the elderly and emphasized the definition of the emergencies from the perspective of those involved. A qualitative research approach was employed, utilizing data gathered from observations, in-depth interviews, demographic information, and group discussions. Initial data access was facilitated through gatekeepers, who selected information providers using purposive sampling, and employed the snowball sampling method to identify individuals with relevant experiences and involvement. A total of 63 participants were involved in this study, comprising local administrative organizations, community leaders, government officials, community members, and elderly individuals. The results revealed three dimensions:1) the perspective of emergency service users, 2) the perspective of emergency service providers, and 3) the perspective of administrators in emergency management for the elderly. Consequently, the emergency medical policy, management strategies, and community nurse competency framework should be adjusted to meet the emergency needs of the elderly in the community, ensuring alignment with the emergency situation within in the community.